Hidden Hematologic Disease in Trauma Patients: A Report of Two Cases - Sung Woo Jang; Pil Young Jung (Journal of Trauma and Injury)
In trauma patients, coagulopathy and abnormal increases or decreases in cell counts are frequently observed, and are associated with high mortality and morbidity in the acute phase of trauma. Because major trauma is often life-threatening, and hematologic abnormalities are multi-factorial and transient, major blood loss is usually suspected to be the primary cause of these abnormalities, and much time and cost may be spent attempting to identify a focus of hemorrhage that might or might not actually exist. Persistent abnormalities in the complete blood count, however, require clinical suspicion of other hematologic diseases to minimize improper transfusions and to improve outcomes, including mortality. Physicians at trauma centers should be familiar with the clinical characteristics of hematologic diseases and should consider these diseases in trauma patients. In this report, we present cases of two hematologic disorders found in trauma patients: autoimmune hemolytic anemia induced by systemic lupus erythematosus and myelodysplastic syndrome.